THE INFLUENCE OF SOCIAL INTERACTION, KNOWLEDGE SHARING, AND PERCEPTIONS OF WORKLOAD ON TEACHER'S READINESS FOR CHANGE AT SMA XYZ-NORTH JAKARTA - Wibowo, Arief; Rakhman, Abdulah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
This study aimed to examine the influence of the variables of social interaction, knowledge sharing, and perceived workload on readiness for change among teachers at SMA XYZ in North Jakarta. The research method used is a quantitative research method. The number of respondents in this study were 38 teachers. The sample used is all teachers who are currently working at SMA XYZ in North Jakarta. The sampling technique is based on nonprobability sampling using the questionnaire method, namely by providing a list of questions directly to the respondents. The analysis method uses Structural Equation Modeling - Partial Least Square (SEM-PLS) with the WarpPLS 7.0 program. The conclusion of this study is that Social Interaction has a negative and significant effect on Readiness for change, Knowledge Sharing has a positive and significant effect on Readiness for change, and Workload Perception has a positive and significant effect on Readiness for Change for teachers at SMA XYZ in North Jakarta.